Scoping Review: The Impact of Local Supplementary Feeding Management Policy on Improving Nutritional Status of Children Under Five - Dita Rasnasuri; Apoina Kartini; Suyatno Suyatno (GLOBAL HEALTH SCIENCE GROUP, 2025)
Malnutrition among children under five remains a significant public health challenge worldwide, particularly in regions with limited access to adequate nutrition. Local supplementary feeding programs have been widely implemented as a strategy to address this issue. However, the effectiveness of these programs is highly dependent on the management policies governing their implementation. Despite the importance of this topic, the literature on the specific impact of these management policies on improving the nutritional status of children under five is fragmented and lacks comprehensive analysis. This study aims to map the literature related to the impact of local supplementary feeding management policies on improving the nutritional status of children under five. The first thousand days of life (1000 HPK) is a critical period that can permanently affect a child’s health and development. Despite ongoing efforts to address nutritional issues, such as stunting, challenges remain in the implementation of effective policies. A scoping review method was applied to explore various studies and related literature, focusing on the impact of nutritional interventions, policies, and local supplementary feeding management. This research was conducted through a systematic literature review, analyzing peer-reviewed articles, reports, and case studies on local supplementary feeding programs. The study focused on identifying the key management policies and their influence on the nutritional outcomes of children under five. Data were synthesized to uncover trends, effective strategies, and gaps in the existing research. The findings underscore the critical need for an integrated approach in nutrition programs, combining effective policy management, community involvement, and sustained resource allocation. Such an approach is essential to optimize the impact of supplementary feeding programs and ensure sustainable improvements in the nutritional status of young children. Future research and policy development should prioritize multi-sectoral collaboration and evidence-based interventions to address persistent challenges in child nutrition.